THE EFFECT OF ENGINE NOISE ON CADETS AT THE INDONESIAN AVIATION ACADEMY VOCATIONAL SCHOOL BANYUWANGI - Prayitno, Hadi; Putra, Dimas Endrawan; Rumani, Daniel D; Rusdiyansyah, Arief; Anam, Muhamad Khoirul (ROTOR, 2023)
Noise is a sound that causes sound violence and disturbs humans. In the aviation industry, noise affects flight safety and success because it can interfere with the concentration and performance of flight cadets. In addition, high intensity can also cause stress and fatigue in flight cadets, reducing their ability to maintain focus and respond to critical situations. This study aimed to analyze the impact of noise produced by engine sounds and radio signals on pilots. The results of this study on the aircraft dashbord sound noise value is greater because the aircraft dashbord clan is located adjacent to the engine while the smallest noise value is found in data retrieval in the back seat because it is farther from the engine. The data collection carried out produces output in the form of data resulting from the effect of engine noise on cadets. Keywords: noise,cadets,engine sound